Non-coding RNA in endothelial-to-mesenchymal transition. Issue 12 (3rd September 2019) - Hulshoff, Melanie S; del Monte-Nieto, Gonzalo; Kovacic, Jason; Krenning, Guido
Abstract: Endothelial-to-mesenchymal transition (EndMT) is the process wherein endothelial cells lose their typical endothelial cell markers and functions and adopt a mesenchymal-like phenotype. EndMT is required for development of the cardiac valves, the pulmonary and dorsal aorta, and arterial maturation, but activation of the EndMT programme during adulthood is believed to contribute to several pathologies including organ fibrosis, cardiovascular disease, and cancer. Non-coding RNAs, including microRNAs, long non-coding RNAs, and circular RNAs, modulate EndMT during development and disease. Here, we review the mechanisms by which non-coding RNAs facilitate or inhibit EndMT during development and disease and provide a perspective on the therapeutic application of non-coding RNAs to treat fibroproliferative cardiovascular disease.